Assessing long-term land use/land cover changes in Dong Thap Province, Upper Vietnamese Mekong Delta: A 33-year retrospective using satellite data - Nguyen, Ho; Trung, Ta Hoang; Dinh, Tran The (Journal of Degraded and Mining Lands Management, 2026)
The Vietnamese Mekong Delta (VMD), Vietnam's “rice bowl”, is a vital agricultural hub due to its extensive network of rivers and fertile floodplains. This study evaluates land use/land cover (LULC) changes in the Upper Delta - Dong Thap Province from 1990 to 2023, using Landsat imagery and random forest algorithms. LULC maps were analyzed across five classes: cropland, wetlands, permanent crops, built-up areas, and open water. We monitored these classes at three points: 1990, 2005, and 2023, noting improvements in classification accuracy from 89% in 1990 to 94% in 2023. Significant transformations were observed; from 1990 to 2005, the most extensive change was the conversion of 477.32 km² of wetlands to cropland. Conversely, the minimal change involved only 0.55 km²  of open water area converted to built-up areas. Between 2005 and 2023, transitions from cropland to permanent crops dominated, peaking at 242.03 km². Over the three decades, the province experienced substantial shifts in LULC, primarily from wetlands to croplands, totaling 513.24 km². These changes reflect both natural dynamics and human impacts, underscoring the influence of past policies on land development. This longitudinal study provides crucial insights for policymakers, emphasizing the need for informed, sustainable land management strategies in Dong Thap Province.